Application of the cost-effectiveness method in improving the pharmacotherapy of multiple myeloma - E. A. Luchinin; M. V. Zhuravleva; T. V. Shelekhova; V. S. Bogova; E. V. Luchinina (Izdatelstvo OKI, 2023)
Multiple myeloma (MM) accounts for 1 % of all cancers and about 10 % of all hemoblastoses. The use of innovative technologies with the inclusion of targeted drugs leads to a significant improvement in the quality of pharmacotherapy and the achievement of overall survival (OS).The aim of the work is to conduct a pharmacoeconomic analysis of the most used MM therapy regimens with the use of targeted drugs and to determine the dominant treatment regimens using a costeffectiveness analysis.Materials and methods. To determine the cost of a course of treatment, we summed up the costs of drugs included in the pharmacotherapy regimen, taking into account taxes, marginal trade markup and duration of the course. Dosing of the targeted drug included in the regimen was determined according to the official instructions for the drug. Progression-free survival (PFS) was adopted as the main criterion for the effectiveness of treatment. Information on PFS of targeted drugs was obtained from data from international phase III RCTs - ASPIRE, TOURMALINEMM1, POLLUX and ELOQUENT2.Results. Based on the results of the pharmacoeconomic analysis, the dominant treatment regimen for MM was determined - daratumumab / lenalidomide / dexamethasone, which has the best cost-effectiveness ratio. The combination of elotuzumab / lenalidomide / dexamethasone was recognized as the least effective technology.